Morphological Features Of River Channels And Floodplains In The Far East Of Russia Under Various Natural Conditions - A.V. Chernov (Zenodo, 2018)
Geographical analysis of river channel processes in rivers located along the meridional transect, running from the Arctic Ocean coast to Tibet and the East China Sea, confirmed that fluvial processes dominate in the formation of morphology and dynamics of river channels and floodplains in all natural zones and under different conditions of channel deformation development. However, even a small disturbance in “climate” conditions by other exogenous geomorphological processes changes the morphology and dynamics of channels and floodplains as well as the dynamics of fluvial processes. The effect of zonal factors depends on the size of a given river and is more pronounced in medium and small rivers than the large ones. Furthermore, the effect of zonal factors on the processes of river channels and floodplains depends on specific environmental conditions of the climate zones: the more extreme the manifestation of certain climatic phenomena, the more pronounced they are in the morphology and dynamics of river channels and floodplains.